2020
DOI: 10.1021/acs.iecr.9b06031
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-67 Membranes Synthesized on α-Al2O3-Plate-Supported Cobalt Nanosheets with Amine Modification for Enhanced H2/CO2 Permselectivity

Abstract: The well-cross-linked ZIF-67 membranes with a thickness of ca. 3 μm were fabricated using α-Al2O3-supported cobalt nanosheets layer (Co-NSL) as an inorganic surface modifier. During the formation of ZIF-67 membranes, Co-NSL served as nucleation centers and cobalt source. Single-gas permeation experiments indicated that the synthesized ZIF-67 membranes showed satisfactory molecular sieving properties, with their H2 permeance reaching 1.48 × 10–6 mol s–1 m–2 Pa–1. The corresponding ideal separation factors of H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…1−3 ZIFs (zeolitic imidazolate frameworks), an important category in MOF materials, possess ultra-microporosities, great chemical stability, and thermostability when compared with other MOFs. 4,5 ZIFs have been widely used to adsorb and separate gases and have also been found in the fields of pervaporation, chemocatalysis, and sensors. 6−12 ZIF-8, the classical ZIF compound that has a sodalite zeolite-type structure, is a suggested candidate material for membranebased applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−3 ZIFs (zeolitic imidazolate frameworks), an important category in MOF materials, possess ultra-microporosities, great chemical stability, and thermostability when compared with other MOFs. 4,5 ZIFs have been widely used to adsorb and separate gases and have also been found in the fields of pervaporation, chemocatalysis, and sensors. 6−12 ZIF-8, the classical ZIF compound that has a sodalite zeolite-type structure, is a suggested candidate material for membranebased applications.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs, that is, metal organic frameworks, exhibit extensive 3D structures and are prepared by linking together the tetrahedral metal ions and the imidazolate linkers. These materials have particular pore sizes, unique chemical properties, and large surface area, which enable them to find utility in the field of separation. ZIFs (zeolitic imidazolate frameworks), an important category in MOF materials, possess ultra-microporosities, great chemical stability, and thermostability when compared with other MOFs. , ZIFs have been widely used to adsorb and separate gases and have also been found in the fields of pervaporation, chemocatalysis, and sensors. ZIF-8, the classical ZIF compound that has a sodalite zeolite-type structure, is a suggested candidate material for membrane-based applications. The in situ growth, secondary seeding growth, and interfacial and vapor-phase processing methods as well as contra-diffusion techniques have so far been explored for MOF membrane synthesis. MOF membranes without defects are not easy to be prepared by the in situ solvothermal approaches because the MOF heterogeneous nucleation density is low in the supports. Support chemistry exerts an important influence on the synthesis of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…We found that only petal-like products (cobalt carbonate hydroxide) existed on the surface of the unmodified support. 41 To solve this problem, we deposited more ZIF-8-IPTMS hybrid materials on the support (Figure 5a), aiming to provide an adequate number of heterogeneous nucleation sites. From the SEM image (Figure 5b), we could observe that the as-prepared ZIF-67 membrane was well intergrown and had no obvious defects compared with the membrane prepared with a relatively low deposition amount of ZIF-8-IPTMS hybrid materials (Figure S8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This result could also be verified by a control experiment in which a ZIF-67 membrane was synthesized on the surface of an unmodified support (Figure S7). We found that only petal-like products (cobalt carbonate hydroxide) existed on the surface of the unmodified support . To solve this problem, we deposited more ZIF-8-IPTMS hybrid materials on the support (Figure a), aiming to provide an adequate number of heterogeneous nucleation sites.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Comparison of the separation performance of our Si-CHA (symbol red ▲) membrane with polymeric membranes with symbol black ● present (a) in the H 2 /CH 4 separation Robeson plot and (b) separation index plot with other membranes: ZIF-67 , with symbol purple ⬟, ZIF-7-8 with symbol gold ⬟, SAPO-34 with symbol black ★, SSZ-13 with symbol black ▲, ZIF-8 with symbol purple ▶, UIO-66 with symbol pink ◀, SAPO-17 with symbol green ■, and HS with symbol red ▼ membranes and mixed-matrix membranes with symbol red ■.…”
Section: Results and Discussionmentioning
confidence: 99%